Impact of periodic intermediary flows on submarine melting of a Greenland glacier. Issue 10 (24th October 2014) - Sciascia, R.; Cenedese, C.; Nicolì, D.; Heimbach, P.; Straneo, F.
Abstract The submarine melting of a vertical glacier front, induced by an intermediary circulation forced by periodic density variations at the mouth of a fjord, is investigated using a nonhydrostatic ocean general circulation model and idealized laboratory experiments. The idealized configurations broadly match that of Sermilik Fjord, southeast Greenland, a largely two layers system characterized by strong seasonal variability of subglacial discharge. Consistent with observations, the numerical results suggest that the intermediary circulation is an effective mechanism for the advection of shelf anomalies inside the fjord. In the numerical simulations, the advection mechanism is a density intrusion with a velocity which is an order of magnitude larger than the velocities associated with a glacier‐driven circulation. In summer, submarine melting is mostly influenced by the discharge of surface runoff at the base of the glacier and the intermediary circulation induces small changes in submarine melting. In winter, on the other hand, submarine melting depends only on the water properties and velocity distribution at the glacier front. Hence, the properties of the waters advected by the intermediary circulation to the glacier front are found to be the primary control of the submarine melting. When the density of the intrusion is intermediate between those found in the fjord's two layers, there is a significant reduction in submarine melting. On the other hand, when the density is close to that of the bottom layer, only a slight reduction in submarine melting is observed. The numerical results compare favorably to idealized laboratory experiments with a similar setup.